Diagnostic Value of GeneChip for Detection of Resistant Mycobacterium tuberculosis in Patients with Differing Treatment Histories - Zhu, Limei (J Clin Microbiol, 2014)
The increasing burden of drug-resistant tuberculosis (TB) poses an escalating threat to national TB control programs. To assist appropriate treatment for TB patients, accurate and rapid detection of drug resistance is critical. The GeneChip test is a novel molecular tool for the diagnosis of TB drug resistance. Performance-related data on GeneChip are limited, and evaluation in new and previously treated TB cases has never been performed. We evaluated the diagnostic performance of GeneChip in detecting resistance to rifampin (RMP) and isoniazid (INH) and in detecting multidrug-resistant tuberculosis (MDR-TB) in comparison with standard drug susceptibility testing (DST) and compared the results in a group of previously treated and newly detected TB patients in an urban area in southeastern China. One thousand one hundred seventy-three (83.8%) new cases and 227 (16.2%) previously treated cases were collected between January 2011 and September 2013. The GeneChip showed a specificity of 97.8% and a sensitivity of 94.8% for detection of RMP resistance and 97.3% and 70.9%, respectively, for INH resistance in new cases. For previously treated cases, the overall sensitivity, specificity, and agreement rate are 94.6%, 91.3%, and 92.1%, respectively, for detection of RMP resistance and 69.7%, 95.4%, and 86.8%, respectively, for INH resistance. The sensitivity and specificity of MDR-TB were 81.8% and 99.0% in new cases and 77.8% and 93.4% in previously treated cases, respectively. The GeneChip system provides a simple, rapid, reliable, and accurate clinical assay for the detection of TB drug resistance, and it is a potentially important diagnostic tool in a high-prevalence area.